Rekonstruksi Pemikiran Pendidikan Islam Antara Tradisi Dan Modernitas - Romadhon, Muhammad Fadli; Mustafidin, Ahmad (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This article discusses the reconstruction of Islamic educational thought in the context of the dynamics between tradition and modernity. Islamic education, as a system rooted in religious values, is faced with the challenges of modernization that demand adaptation and innovation. This study aims to analyze how Islamic educational thought can be reconstructed to remain relevant to the development of the times without losing the essence of its traditional values. Through a literature review approach and comparative analysis, this article explores the various thoughts of Islamic educational figures, both classical and contemporary, in responding to the challenges of modernity. This article also identifies key elements in the Islamic educational tradition that need to be maintained and developed, and offers a conceptual framework for reconstructing integrative and progressive Islamic educational thought. The results of the study indicate that the reconstruction of Islamic educational thought requires a balance between maintaining noble traditional values and adopting positive modern innovations. This article emphasizes the importance of developing a holistic curriculum, innovative teaching methods, and a comprehensive evaluation system, as well as improving the quality of educators. Thus, Islamic education can contribute significantly to forming a generation that is faithful, knowledgeable, and has noble character, and is able to face global challenges.